The Influence of Digital Public Service Innovation Through the BSB Mobile Application on Community Satisfaction in Palembang City - Putri Lianti; Annada Nasyaya (Jurnal Studi Sosial dan Politik, 2025)
The Indonesian government is committed to accelerating the digital transformation of the public service sector as part of the bureaucratic reform agenda thru PERMENPAN RB Number 91 of 2021. Bank Sumsel Babel, as one of the providers of public service innovations, offers digital banking services in the form of the bsb mobile application. Although the BSB Mobile application is presented as a digital public service innovation to facilitate banking transactions, various user complaints have been found regarding system disruptions, service access issues, and application usage experiences that could potentially affect public satisfaction levels. This study aims to determine and analyze the effect of digital public service innovation through the BSB Mobile application on community satisfaction in Palembang. The research method employed is a quantitative approach, with data collected through questionnaires distributed to users of the BSB Mobile application in Palembang via Google Forms. The data were analyzed using multiple linear regression with the assistance of SPSS version 27 software. The results indicate that digital public service innovation through the BSB Mobile application has a positive and significant effect on community satisfaction. This is evidenced by the t-count value being greater than the t-table value (14.392 > 1.985) and the significance value being lower than 0.05 (<0.001 < 0.05). Furthermore, the coefficient of determination (R²) value of 0.693 indicates that digital public service innovation, along with the control variables of age, duration of application usage, and frequency of application usage within one month, explains 69.3% of community satisfaction, while the remaining 30.7% is influenced by other factors outside the scope of this study. These findings confirm that digital public service innovation plays an important role in enhancing community satisfaction, particularly in the use of application-based services such as BSB Mobile.